Follow-Up Results of Our Patients with Rheumatoid Arthritis - Tuğba YALÇIN,; Ajda BAL,; Deniz DÜLGEROĞLU,; Aytül ÇAKCI, (Archives of Rheumatology, 2012)
Objectives: The aims of this study were to evaluate demographic and clinical characteristics of the patients with rheumatoid arthritis (RA), to compare laboratory, clinical, radiographic, and functional parameters at baseline and the last visit and to demonstrate changes in the functional status and radiographic grading. Patients and methods: The files of 441 patients with RA who were followed in our Rheumotology Outpatient Clinic between January 2003 - December 2009 were retrospectively analyzed. The demographic and clinical characteristics as well as follow-up parameters at baseline and the last visit were recorded. In laboratory investigations, erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) values were established. Disease activity, functional level and radiographic grading were determined using Disease Activity Score involving 28 joints (DAS28), Health Assessment Questionnaire (HAQ) and Larsen Score with anterior-posterior hand X-rays, respectively. Results: Significant improvements were found in DAS28 and HAQ levels at the last visit, compared to baseline (p<0.001), while no significant change was observed in Larsen scores (p=0.484). Significant improvements were also observed only in CRP values at the last visit, compared to baseline (p<0.001). DAS28 scores of the patients without extra-articular involvement with a good compliance were found to be lower than in the others at the last visit (p=0.043, p<0.001). Conclusion: Our results indicate that disease-modifying antirheumatic drug (DMARD) treatment in combination with regular follow-up is of utmost importance for the suppression of the disease activity in RA patients. Patients should be educated on drugs, as those with good compliance showed a better disease activity level.